Causal Relationship Model of Four Noble Truths - Thiengkamol, Nongnapas (Mediterranean Journal of Social Sciences, 2012)
The objective was to propose the structural model of four noble truths affecting to environmental behavior for global warming alleviation through inspiration of public consciousness.The populations were 37,156 undergraduate student of Mahasarakham University in first semester of academic year of 2012. The Multi-stage simple random sampling technique was employed to collect the sample for 400 undergraduate students. The research instrument was the questionnaire and it was used for data collecting. LISREL was used for model verification. Results illustrated that structural model of confirmatory factors of Four Noble Truths (FNT) was able to explain the variation of endogenous factors of Inspiration of Public Consciousness (INS) to caused Environmental Behaviors for Global Warming Alleviation (BEH) with 89.0 percents as following. BEH = 0.45 FNT + 0.53 INS ……………………..(1) (R2 = 0.89) Equation (1) factors that had the most effect to Environmental Behaviors for Global Warming Alleviation (BEH) was Inspiration of Public Consciousness (INS) and subsequence was Four Noble Truths (FNT). These were able to explain the variation of Environmental Behaviors for Global Warming Alleviation (BEH) with 89.00 percents.